A systematic review and functional in-silico analysis of genes and variants associated with amyotrophic lateral sclerosis - Arreola-Aldape, Carlos A.; Moran-Guerrero, Jose A.; Pons-Monnier, Guillermo K.; Flores-Salcido, Rogelio E.; Martinez-Ledesma, Emmanuel; Ruiz-Manriquez, Luis M.; Razo-Alvarez, K. Rebeca; Mares-Custodio, Daniela; Avalos-Montes, Pablo J.; Figueroa-Sanchez, Jose A.; Ortiz-Lopez, Rocio; Martínez, Hector R.; et al. (Frontiers in Neuroscience, 2025)
IntroductionAmyotrophic lateral sclerosis (ALS) is a fatal progressive neurodegenerative disease characterized by the deterioration of upper and lower motor neurons. Affected patients experience progressive muscle weakness, including difficulty in swallowing and breathing; being respiratory failure the main cause of death. However, there is considerable phenotypic heterogeneity, and its diagnosis is based on clinical criteria. Moreover, most ALS cases remain unexplained, suggesting a complex genetic background.MethodsTo better understand the molecular mechanisms underlying ALS, we comprehensively analyzed, filtered and classified genes from 4,293 abstracts retrieved from PubMed, 7,343 variants from ClinVar, and 33 study accessions from GWAS catalog. To address the importance of ALS-associated genes and variants, we performed diverse bioinformatic analyses, including gene set enrichment, drug-gene interactions, and differential gene expression analysis using public databases.ResultsOur analysis yielded a catalog of 300 genes with 479 ALS-associated variants. Most of these genes and variants are found in coding regions and their proteins are allocated to the cytoplasm and the nucleus, underscoring the relevance of toxic protein aggregates. Moreover, protein-coding genes enriched ALS-specific pathways, for example spasticity, dysarthria and dyspnea. ALS-associated genes are targeted by commonly used drugs, including Riluzole and Edaravone, and by the recently approved antisense oligonucleotide therapy (Tofersen). Moreover, we observed transcriptional dysregulation of ALS-associated genes in peripheral blood mononuclear cell and postmortem cortex samples.ConclusionOverall, this ALS catalog can serve as a foundational tool for advancing early diagnosis, identifying biomarkers, and developing personalized therapeutic strategies.